Augmented Reality Teaching Resources and Its Implementation in the Teaching-Learning Process - Cóndor-Herrera, Omar (2021)
This work presents a revision of possible applications of the augmented reality in the scholar context, such as the utilization of augmented reality to improve reading comprehension or its application in geometry learning and many others. At the same time, as a contribution to the research field, there is a proposal about the design and development of didactical resources that count with augmented reality objects, images, or illustrative graphs, as well as multimedia videos to improve the teaching-learning process of various academic topics.